Regioselective Transition-Metal-Catalyzed C–H Functionalization of Anilines - Leitch, Jamie A.; Frost, Christopher G. (Synthesis, 2018)
Anilines are a vital synthetic core of pharmaceuticals, agrochemicals, natural products and building blocks. Metal-catalyzed C–H functionalization has emerged as a powerful tool to derivatize biologically relevant molecules. To this end, the derivation of anilines via catalytic C–H functionalization has been the subject of important new synthetic methodology. This review focuses on the tactics used to allow regioselective C–H functionalization of anilines.1 Introduction2 ortho-Selective C–H Functionalization2.1 Palladium2.2 Rhodium2.3 Ruthenium2.4 Nickel3 meta-Selective C–H Functionalization4 para-Selective C–H Functionalization5 Conclusion
Keywords: C–H functionalization; homogeneous catalysis; anilines; regioselectivity; aromatic